Caregivers' Knowledge, Attitude, and Practice towards Pressure Injuries in Spinal Cord Injury at Rehabilitation Center in Bangladesh. (14th June 2022) - Tharu, Niraj Singh; Alam, Monzurul; Bajracharya, Shristi; Chaudhary, Gautam Prasad; Pandey, Jitendra; Kabir, Mohammad A.
Abstract : The purpose of this study was to determine caregivers' knowledge, attitude, and practice (KAP) on the prevention and care of pressure injuries (PIs) in individuals with spinal cord injury. A quantitative cross-sectional study with descriptive correlation design was used to implement a modified semistructured questionnaire using a convenient sampling method. McDonald's standard of learning outcome measurement criteria was used to categorize caregivers' KAP. A Pearson product-moment correlation coefficient ( r ) was utilized to assess the relationships between caregivers' KAP, with a p value of 0.05 or less considered statistically significant. The study findings indicate that caregivers had a moderate level of knowledge (M = 73.68%, SD = 6.43), a neutral attitude (M = 70.32%, SD = 6.89), and a moderate level of practice (M = 74.77%, SD = 9.08). A positive correlation existed between caregivers' knowledge and attitude ( r  = 0.30, p < 0.01 ), as well as between knowledge and practice ( r  = 0.37, p < 0.01 ). Nevertheless, there was no correlation between attitude and practice ( r  = 0.12, p > 0.05 ). The study findings suggest that caregivers need to develop a positive attitude and expand their knowledge in order to improve their practice. The KAP factors that require higher priority were positioning and turning the patient, preventing skin breakdown, assessing weight changes over time, interest in patient care, additional care for PIs, frequently changing the individual's position, priority to PI care, interest in other types of care other than PIs, using special cushions, consulting doctors on a regular basis, being aware of clothing and fabrics, proper transfer technique, pressure relief, and skin inspection, among others.